2015
DOI: 10.3109/09637486.2014.986073
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of omega 3 fatty acids improves oxidative stress in activated BV2 microglial cell line

Abstract: Many reports have shown promising beneficial effects of long-chain polyunsaturated fatty acids (L-PUFAs) of the omega 3 series in several brain diseases. In the present study, we tested the hypothesis that omega 3 fatty acids supplement reduced pro-inflammatory functions in vitro and in vivo. We demonstrated that a supplement rich in PUFAs (SRP) increased cell viability in a dose-dependent manner suggesting its protective role against lipopolysaccharide (LPS)-induced cell death in BV2 microglial cell line. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 33 publications
4
20
0
Order By: Relevance
“…We found that fish oil supplementation for 12 weeks to PCOS women upregulated gene expression of PPAR‐γ, but unchanged GLUT‐1 expression. In agreement with our study, the chronic administration of omega‐3 fatty acids to rats increased the immunoreactivity of the PPAR‐γ1 protein . We have previously shown that omega‐3 fatty acids supplementation from flaxseed oil for 12 weeks to subjects with PCOS improved gene expression of PPAR‐γ, but did not affect gene expression of GLUT‐1 .…”
Section: Discussionsupporting
confidence: 91%
“…We found that fish oil supplementation for 12 weeks to PCOS women upregulated gene expression of PPAR‐γ, but unchanged GLUT‐1 expression. In agreement with our study, the chronic administration of omega‐3 fatty acids to rats increased the immunoreactivity of the PPAR‐γ1 protein . We have previously shown that omega‐3 fatty acids supplementation from flaxseed oil for 12 weeks to subjects with PCOS improved gene expression of PPAR‐γ, but did not affect gene expression of GLUT‐1 .…”
Section: Discussionsupporting
confidence: 91%
“…The membrane reorganization consequence of DHA increase is in line with in vitro data showing that DHA modulates the activation of several proinflammatory transcription factors (NFkB; mitogen-activated phosphate kinase p38; c-Jun N-terminal kinases) in microglia (De Smedt-Peyrusse et al, 2008;Ma et al, 2009;Lu et al, 2013;Chang et al, 2015). In microglia, DHA upregulates peroxisome proliferator-activated receptor (PPAR)g nuclear translocation, a potent modulator of microglia (Ajmone-Cat et al, 2010;Corsi et al, 2015).…”
Section: B Overview Of Dha Anti-inflammatory/ Proresolving Mechanismssupporting
confidence: 62%
“…Briefly, whatever the inflammatory challenge applied on these cells (TLR3-4 or 7 agonists, Ab, interferon-g, hypoxia, or myelin), all studies reported a dose-dependent decrease in the production of proinflammatory factors (cytokines and/or chemokines) when treated with n-3 PUFAs (De Smedt-Peyrusse et al, 2008). N-3 PUFAs also inhibit the production and activity of the enzymes COX-2, iNOS, and the production of NO and reactive oxygen species (Moon et al, 2007;Lu et al, 2010;Antonietta Ajmone-Cat et al, 2012;Pettit et al, 2013;Chen et al, 2014;Corsi et al, 2015;Zendedel et al, 2015). This is correlated with a switch in microglial marker expression, from a proinflammatory to an anti-inflammatory phenotype (decreased CD40 and CD86, increased CD206) (Ebert et al, 2009;Chhor et al, 2013;Hjorth et al, 2013;Chen et al, 2014).…”
Section: Microglia As a Target For N-3 Pufas And Spmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Omega-3 fatty acids and especially docosahexaenoic acid (DHA) are natural products which can be taken as dietary supplements, and have been shown to act throughout nuclear PPAR-γ receptors on dendritic cells, modulating their inflammatory activity [ 26 ] and converting dendritic cells in poor stimulators of antigen-specific T-cells in terms of proliferation and Th1/Th17 differentiation [ 3 ]. Furthermore, these fatty acids have shown modulation of the inflammatory properties of activated microglia [ 11 , 27 , 28 , 29 ] and amelioration of neurodegenerative diseases involving neuroinflammation [ 30 , 31 ]. The objective of this study was to determine the capacity of the triglyceride form of natural DHA (TG-DHA), which has shown improved bioavailability [ 32 , 33 ], as compared to the ethyl ester form to modulate the proinflammatory activity of in vitro cultured microglial cells, as well as to assess the effect of TG-DHA in the course of the disease in a mice model of EAE [ 12 ].…”
Section: Introductionmentioning
confidence: 99%